Using the Narrative Approach with Adolescents at Risk for Suicide - MacLeod, Michael (Canadian Journal of Counselling and Psychotherapy, 2019)
Treatment approaches exist for adolescents who have attempted suicide or have expressed thoughts of suicide. Many of these interventions position the counsellor as the expert, focus primarily on what is not working, provide little collaboration with adolescents regarding treatment, and do not empower adolescents to tell their story. A review of the literature revealed that the narrative approach addresses these deficits, but it is not often used with adolescents at risk for suicide. To address this concern, empirical treatment approaches were reviewed, suggestions were presented for implementing the narrative approach systematically, and recommendations were offered for future research.